The Chemistry Department at Imperial College, London a history, 1845-2000 - Gay, Hannah; Griffith, W. P. (William Pettitt), 1936- (London : World Scientific Publishing Europe Ltd., 2017)
'This is the first comprehensive history of the chemistry department at Imperial College London. Based on archival records, oral testimony, published papers, published and unpublished memoirs, the book tells the story of this world-famous department from its foundation as the Royal College of Chemistry in 1845 to the large department it had become by the year 2000. The book covers research, teaching, departmental governance, students and social life. It also highlights the extraordinary contributions made to the war effort in both the first and second world wars. From its first professors, A. Wilhelm Hofmann and Edward Frankland, the department has been home to many eminent chemists, including, in the later twentieth century, the Nobel laureates Derek Barton and Geoffrey Wilkinson. New information on these and many others is presented in a lively narrative that places both people and events in the larger historical contexts of chemistry, politics, culture and the economy. The book will interest not only those connected with Imperial College, but anyone interested in chemistry and its history, or in higher'--Publisher's website.
Title from PDF file title page (viewed November 16, 2016).
Includes bibliographical references and index.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Imperial College, London. {u01C2}b Chemistry Department.61020Imperial College of Science, Technology and Medicine. -- Department of Chemistry; Imperial College of Science and Technology. -- Department of Chemistry; Royal College of Chemistry (Great Britain); Imperial College, London -- History; Chemistry -- Study and teaching (Higher) -- Great Britain; Electronic books